Hope in Severe Disease: A Review of the Literature on the Construct and the Tools for Assessing Hope in the Psycho-oncologic Setting. Issue 5 (September 2015) - Piccinelli, Claudia; Clerici, Carlo Alfredo; Veneroni, Laura; Ferrari, Andrea; Proserpio, Tullio
Aims and background: Research on the topic of hope began a long time ago but, more recently, interest in this construct has focused mainly on the development of psychometric tools for its assessment. The 2 steps of the present article are defining the construct of hope by completing a preliminary review of the literature and analyzing the tools used to assess hope in the setting of oncologic medicine, conducting a systematic review of the existing scientific literature. Methods and Study Design: Our study was conducted in 2 stages. The first stage involved a nonsystematic preliminary review of the literature, the second a systematic search in all the medical journals contained in the Medline database as of 2012. The literature identified at the first stage was divided according to several topical categories, i.e., theoretical, empirical, and clinical works on the construct of hope. In the second systematic search, we identified the main psychometric tools used to measure hope in the field of clinical oncology and assessed their validity. Results: A total of 22 articles were identified. What emerged when we pooled the findings of our 2 lines of research was that, despite its broad theoretical definitions, the construct of hope can be broken down to a few constituent elements when hope is studied using currently available psychometric tools. In particular, these identified constituent elements were coping, spiritual well-being, quality of life, distress, and depression. Conclusions: The factors contained in the construct of hope include temporality, future, expectancy, motivation, and interconnectedness. The review of the scientific literature does not reveal a clear definition of hope. Multidisciplinary studies are needed to communicate different perspectives (medical, psychological, spiritual, theological) among each other for better definition of the constituent elements of hope in order to support the hope with specific interventions.